Mo jībana saṅgrāma, 1934 ru 1984 : arddhaśatābdīra samājabādī āndoḷanara kāhāṇī - Dwivedy, Surendranath (Grantha Mandira, 1984)
Autobiography of an Indian freedom fighter and parliamentarian; chiefly about his involvement in the socialist movement in India, 1934-1984